The issues of diaspora and displacement in Elif Shafak's The Island of Missing Trees (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This paper aims to analyse the issues of diaspora and displacement in Elif Shafak’s The Island of Missing Trees. The novel focuses on the Kazantzakis family that is forced to flee their homeland Cyprus to England. A unique aspect of the novel is that half of it is narrated by a fig tree. Therefore, this novel will be analysed both from Multicultural and Ecocritical perspectives. To analyse the data, this research uses a qualitative descriptive method, particularly textual analysis. In the end, the result of this paper shows a connection between the issues of diaspora and displacement with natural environment. This analysis is important because in the 21st century conflicts are still happening, which force people to leave their homeland and significantly affect the natural environment.